Inovasi Proses Ramah Lingkungan Pada Usaha Omah Batik Srikandi Dan Edukriya Keluruhan Jatisari Kecamatan Mijen Kota Semarang - Sulistiyani Sulistiyani; Sri Suprapti (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Service activities were held at the Omar Batik Srikandi Gallery and the Edukriya Jatisari Gallery in Jatisari District, Mijen District, Semarang City. This service activity is one of the supporting activities to provide services to the community, namely to the batik business in terms of environmentally friendly process innovation. The aim of this service is to develop the batik business and gain market share through environmentally friendly process innovation. Omar Batik Srikandi and Edukriya Jatisari galleries are facing the problem of steady or stagnant demand with a small number of unsuccessful requests. From the results of discussions between the community service team and the community, the Omah Batik Srikandi Jatisari Gallery is trying to maximize innovation in environmentally friendly processes to develop ideas sourced from themselves and others in dealing with waste from batik dyes, but has not yet implemented environmentally friendly process innovations. maximum. The service method is implemented through knowledge consultation about environmentally friendly process innovations so that green innovations can be developed to reduce batik dye waste in rivers.